Kinerja Pegawai Berdasarkan Aspek Kepemimpinan Transformasional, Budaya Organisasi, dan Inovasi (Studi Kasus Dinas Syariat Islam Kabupaten Bireuen) - Samsurizal Samsurizal; Evi Arief Syarifuddin; Laina Fadhilah; M. F. Chadafi (Singkite Journal, 2026)
Employee performance is suspected to be directly and indirectly related to several factors, including transformational leadership, organizational culture, and employee innovation. This research was conducted using a case study of employees at the Bireuen Regency Sharia Office. This study applied a quantitative associative method and used path model statistics to analyze the data. The results showed that: (1) employee performance is directly and indirectly influenced by the causality of transformational leadership (37.52%), organizational culture variables (31.36%), and employee innovation (34.3%). (2) transformational leadership, Organizational culture, and innovation factors collectively impact employee performance by 60,3%. (3) There is a causal relationship between the variables of, transformational leadership, organizational culture, and innovation, with a fairly strong categorization